2021
DOI: 10.1080/09638288.2021.1910737
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based stroke rehabilitation: do priorities for practice change and feasibility of implementation vary across high income, upper and lower-middle income countries?

Abstract: Evidence-based stroke rehabilitation: do priorities for practice change and feasibility of implementation vary across high income, upper and lower-middle income countries? Disability and Rehabilitation .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition to lack of rehabilitation specialists, competing healthcare demands in LMICs also leads to difficulty growing capacity for stroke rehabilitation. A study of healthcare providers’ priorities and their perceptions regarding the feasibility of implementing those priorities demonstrated that healthcare workers from HICs were in a better position to prioritize, facilitate, and implement specialized stroke rehabilitation services while healthcare providers from LMICs were more supportive of the intensification of existing rehabilitation services, however vague, because of the expense associated with developing specialized services 8 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to lack of rehabilitation specialists, competing healthcare demands in LMICs also leads to difficulty growing capacity for stroke rehabilitation. A study of healthcare providers’ priorities and their perceptions regarding the feasibility of implementing those priorities demonstrated that healthcare workers from HICs were in a better position to prioritize, facilitate, and implement specialized stroke rehabilitation services while healthcare providers from LMICs were more supportive of the intensification of existing rehabilitation services, however vague, because of the expense associated with developing specialized services 8 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…Furthermore, rehabilitation therapists available in LMICs are more likely to have a multidisciplinary focus rather than a focus on stroke alone and to be entry-level therapists with limited experience, thus further compromising rehabilitation options available to individuals with stroke 8,12 . Ultimately, lack of specialized personnel and standardized overarching structures for rehabilitation services in combination with limited expertise for stroke rehabilitation and poor processes leads to poor quality services and, ultimately, poor patient outcomes 13 …”
Section: Barriers To Stroke Rehabilitation In Lmicsmentioning
confidence: 99%
“…Stroke has a negative impact on the physical, emotional, social, and economic wellbeing of caregivers (Karahan et al, 2014;Hu et al, 2018;Owolabi et al, 2021;Gururaj et al, 2022), which significantly affects the health outcomes and quality of life of stroke survivors (Adelman et al, 2014). The Evidence has suggested that 25-46% of caregivers experience significant distress during the first 6 months of care in the transition from facility-based to home-based care (Blake et al, 2003;Tooth et al, 2005;Van Exel et al, 2005;Ilse et al, 2008), which is often associated with disease severity, depressive and anxiety symptoms, sex, duration and intensity of care, and degree of disability of stroke patients (Blake et al, 2003;Choi-Kwon et al, 2005;Ilse et al, 2008;Bhattacharjee et al, 2012;Gbiri et al, 2015;Jaracz et al, 2015;Kumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Poor economic status and health care services could be possible reasons for the increased caregiver burden in a resource-limited setting. Shifting responsibility to health professionals, families, and available community-based rehabilitation providers is a costeffective strategy to improve the access and quality of poststroke rehabilitation in resource-constrained areas, particularly in Ethiopia (Gururaj et al, 2022;Kayola et al, 2023). Caregivers are therefore encouraged to be actively engaged in post-stroke rehabilitation with the aim of preventing complications and improving the quality of life of the survivors.…”
Section: Introductionmentioning
confidence: 99%